(untitled) (Global Journal of Human-Social Science, 2024)
This interdisciplinary quantitative study examines the influence of visits to Civil War shelters in Alicante on the perception of memory-based cultural heritage within an urban context. Through the analysis of 407 visitors from August 2023 to January 2024, it investigates how the rehabilitation and opening of these spaces contribute to sustainable urban development and historical understanding. Preliminary results show an increase in interest and awareness of the historical importance of the shelters, indicating a positive impact on the valuation of memory heritage. The study highlights the correlation between the provision of cultural and educational activities and the increase in visitors, underscoring the need for differentiated communication and management strategies to attract diverse visitor profiles. This analysis provides key insights for the management of cultural heritage and suggests improved approaches for the promotion of historical legacy.